Documenting decapod biodiversity in the Caribbean from DNA barcodes generated during field training in taxonomy - Venera-Pontón, D; Driskell, A; De Grave, S; Felder, D; Scioli, J; Collin, R (Pensoft Publishers, 2020)
DNA barcoding is a useful tool to identify the components of mixed or bulk samples, as well as to determine individuals that lack morphologically diagnostic features. However, the reference database of DNA barcode sequences is particularly sparsely populated for marine invertebrates and for tropical taxa. We used samples collected as part of two field courses, focused on graduate training in taxonomy and systematics, to generate DNA sequences of the barcode fragments of cytochrome c oxidase subunit I (COI) and mitochondrial ribosomal 16S genes for 447 individuals, representing at least 129 morphospecies of decapod crustaceans. COI sequences for 36% (51/140) of the species and 16S sequences for 26% (37/140) of the species were new to GenBank. Automatic Barcode Gap Discovery identified 140 operational taxonomic units (OTUs) which largely coincided with the morphospecies delimitations. Barcode identifications (i.e. matches to identified sequences) were especially useful for OTUs within Synalpheus , a group that is notoriously difficult to identify and rife with cryptic species, a number of which we could not identify to species, based on morphology. Non-concordance between morphospecies and barcode OTUs also occurred in a few cases of suspected cryptic species. As mitochondrial pseudogenes are particularly common in decapods, we investigate the potential for this dataset to include pseudogenes and discuss the utility of these sequences as species identifiers (i.e. barcodes). These results demonstrate that material collected and identified during training activities can provide useful incidental barcode reference samples for under-studied taxa.